(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article analyzes the development directions of the modern education system, its role in social progress, and mechanisms for improving educational quality. The study examines modernization of the education system, implementation of innovative pedagogical approaches, and integration of digital technologies into the educational process. Furthermore, the strategic importance of education in enhancing management efficiency and developing human capital is substantiated. The research findings contribute to developing scientific and practical recommendations aimed at improving the educational process.